Mathematical model for the power supply system of an autonomous object with an AC power transmission over a cable rope - Rulevskiy V. M.; Bukreev V. G. Viktor Grigorievich; Shandarova E. B. Elena Borisovna; Kuleshova E. O. Elena Olegovna; Shandarov S. M.; Vasilyeva Yu. Z. (Numerical simulation of applied problems, 2017)
Title screen